THE OFFENCE OF MASS DISORDER IN THE CRIMINAL LAWS OF SOME EUROPEAN STATES - Valentin Chirița; Ana-Maria Chepestru (Revija za kriminologiju i krivično pravo)
The legal system of each state consists of a wide range of legal rules. Thus, national security and legal order are a high priority for each nation and manifest themselves distinctly within any state. In the Republic of Moldova, the mentioned social value is protected both: the contravention and by the criminal law. This paper aims to make a study of the crime of mass disorder in the Republic of Moldova in comparison with European countries. The comparative analysis of the crime will contribute to the examination of European legal norms and to the research of the possibility of including some provisions in the legal framework of the Republic of Moldova. Similarly, the good practices of European countries will be taken into account through the elements of comparative criminal law.